Abnormal plasma fibrinolysis in patients with rheumatoid arthritis and impaired endothelial fibrinolytic response in those complicated by vasculitis. Issue 9 (September 1993) - Lau, C S; McLaren, M; Hanslip, J; Kerr, M; Belch, J J
Abstract : OBJECTIVES--(a) To assess plasma fibrinolytic parameters in patients with rheumatoid arthritis (RA) and to determine whether there are differences between patients with RA alone and those with RA complicated by vasculitis. (b) To determine if patients with RA respond differently to venous occlusion compared with normal subjects and to assess whether such a response differs in patients with RA alone and those with rheumatoid vasculitis. (c) To determine the extent of vascular damage in patients with rheumatoid vasculitis and if this correlates with the levels of plasma fibrinolytic parameters. METHODS--Sixty three patients with RA (38 had RA only and 25 had evidence of rheumatoid vasculitis) were recruited. Plasma levels of tissue plasminogen activator antigen (t-PA Ag), plasminogen activator inhibitor (PAI) activity, and factor VIII von Willebrand factor (vWF) were measured before and 10 minutes after venous occlusion. RESULTS--Patients with RA, with or without rheumatoid vasculitis, had higher baseline PAI levels than control subjects. The difference was statistically significant for patients with RA alone but was not statistically significant for patients with rheumatoid vasculitis. After venous occlusion, t-PA Ag levels increased significantly in normal subjects and patients with RA alone, but not in patients with rheumatoid vasculitis. Plasma levels of vWF were significantly higher in patients with rheumatoid vasculitis than in normal subjects and those with RA alone. In patients with RA alone, baseline vWF correlated positively with t-PA Ag levels, whereas a negative correlation was found between these two parameters in patients with rheumatoid vasculitis. A negative correlation between vWF and t-PA Ag levels after venous occlusion was also found in patients with rheumatoid vasculitis. CONCLUSIONS--Patients with rheumatoid vasculitis showed evidence of vascular damage with increased levels of vWF and impaired t-PA Ag release after venous occlusion, a useful measurement of endothelial reserve to remove fibrin. This may be of pathophysiological importance in the development of vasculitis in these patients.